Persepsi Gamers tentang Aktivitas Microtransactions di Virtual Goods Marketplace Itemku.com - Vikry Abdullah Rahiem; Charisma Asri Fitrananda (Fakultas Ilmu Komunikasi Universitas Pancasila, 2021)
The growth of games as a fast growing industry in Indonesia has made online gaming business lines increasingly developed, so that a business market for buying and selling virtual goods (virtual items in games) is formed in several virtual goods marketplaces such as itemku.com. The formation of the business market on the virtual goods marketplace has created various perceptions to support their gaming activities. This study uses qualitative methods, observation techniques, in-depth interviews and documentation. The theory used is perception. This study will discuss how variables such as sensation, anticipation and interpretation are formed from gamers about how microtransactions are carried out and also associated with CMC (Computer Mediated Communcations) to find out how communication patterns occur in these mictrotransactions. As a result, the majority of gamers have the same perception of microtransactions. Gamers who make virtual goods transactions aim to get satisfaction as well as actualization, virtual items that have more value in the game also trigger to perform microtransactions as part of the pride, and factor of self-existence when doing gaming activities using CMC.